The attack on Ukraine and the militarisation of Russian Foreign and domestic policy: A stress test for military reform and regime legitimacy - Margarete Klein; Nils Holger Schreiber (Stiftung Wissenschaft und Politik (SWP), 2022)
Moscow's decision on 24 February 2022 to invade Ukraine constituted a culmination in the militarisation trajectory of Russian foreign policy since 2008. At the same time, the war has exposed the weaknesses of the military reform launched by Moscow in 2008. The high losses of the country's armed forces in Ukraine limit Russia's military power projection capabilities, for example in Syria and in other conflicts. Moreover, military setbacks and partial mobilisation have undermined an important pillar of the regime's legitimacy.
Keywords: 320; Ukraine; Russia; Vladimir Putin; military reform; invasion; war of aggression; militarisation of foreign policy; regime legitimacy; mobilisation